3D printing and post-curing optimization of photopolymerized structures: Basic concepts and effective tools for improved thermomechanical properties. (April 2022) - Štaffová, Martina; Ondreáš, František; Svatík, Juraj; Zbončák, Marek; Jančář, Josef; Lepcio, Petr
Abstract: The final thermo-mechanical properties of structural parts fabricated by masked stereolithography (MSLA) are highly determined not only by the processing parameters, but also by the post-processing methods. Improper implementation of post-treatment often leads to underperforming printouts. A novel tool for complex characterization of 3D printed bodies was developed and systematically demonstrated on a commercial free-radical photopolymerization (FRP) resin. The method relies on superimposed static and oscillatory mechanical test combining the heat deflection temperature (HDT) measurement together with the dynamic mechanical analysis (DMA) in a single test for fast and reliable characterization of parameters determining the curing behaviour of the photopolymer. The influence of post-curing time was addressed with a special focus on network density. Furthermore, the print orientation, having a high impact on mechanical properties, is discussed with a particular regard on the residual stress mitigation in future applications, such as 3D-printed cellular bodies. Highlights: Development of a combined DMA-HDT technique for photo-cured resin characterization. Network density as the key parameter to control thermomechanical properties. Evaluation of the curing time, print orientation and sample thickness influence on final properties. Conversion profile along the specimen depth determined by FTIR-ATR.